Relations Between Servant Leadership and Middle Management Competencies - Gedvilienė, Genutė; Supranavičienė, Ugnė (Pedagogika, 2023)
This study aims to reveal the relations between servant leadership (SL) and middle managers (MM) competencies in organisation. The study was constructed as qualitative research with assessments and focus group discussion. The results showed some managers are able to apply competencies typical for MM and there is a relation with SL competencies, but analysing relation between MM and the organisation identified the lack of organisation systematic approach for MM leadership development.